The conservation of urban flower visitors Down Under - Iwasaki, Jay M.; Hogendoorn, Katja (Frontiers in Sustainable Cities, 2023)
The majority of the human population now lives in urban environments and that proportion is forecast to increase dramatically by 2050. As urbanisation increases, the urban environment will increasingly play a role in biodiversity conservation. Floral visitors, often erroneously referred to as pollinators, are integral to the maintenance of ecosystem services and function. Several floral visitors are capable of adapting to urban environments, but for comprehensive protection, management practices must be tailored to specific groups. Urban biodiversity conservation is usually discussed from the northern hemisphere perspective, which has a very different ecology than its southern counterpart. Here we compare and contrast conservation strategies for urban flower visitors in Australia and New Zealand to the northern hemisphere, with a focus on birds and bees. The differences in flower visitors and floral characteristics mean that unique management strategies, which consider the local evolutionary context and integrate native flora, are required to support urban flower visitors. An additional important difference is that neither honey bees nor bumble bees, which reach high local densities in many areas, are native to the region, and thus should be excluded from urban biodiversity schemes.